Children’s favorite places on the kindergarten playground – according to the staff - Anikke Hagen; Hilde Nancy Skaug,; Kari Synnes (JETEN, 2019)
The aim of this study was to investigate Norwegian early childhood teachers’ perceptions about where on the kindergarten’s outdoor playground the children prefer to play, and what characterizes these places. A questionnaire was used to provide quantitative data. 854 Norwegian Kindergarten principals or pedagogical leaders from all over the country have answered the questionnaire. The functional affordance taxonomy is the basis for the question. The finding indicates that early childhood teachers consider places with a feature of nature as the most attractive`, and fixed play equipment were the least attractive places for children’s outdoor play.